When DRM Meets Restricted Multicast: A Content Encryption Key Scheme for Multicast Encryption and DRM - Feng, Min; Zhu, Bin Benjamin (IEEE Consumer Communications and Networking Conference, 2007)
In many applications it is desired to save the content received from restricted broadcast or multicast to local files for subsequent replays. The locally saved files should be protected by a Digital Rights Management (DRM) system to prevent unauthorized usage. It is a great challenge to combine DRM with restricted broadcast or multicast since they are designed for different applications. In this paper, we first present two straightforward solutions and discuss their drawbacks. We then present a novel content encryption key scheme for restricted broadcast and multicast that facilitates subsequent DRM protection for the saved content. It enables direct saving of encrypted content to local files and easy generation and management of decryption keys for replays of saved files. Only a single key needs to be delivered to a client in a license. Security of the proposed key scheme is analyzed, and comparison of the three methods in also discussed in this paper.